Map showing location and designation of Indian reserves in the North West Territories and the province of Quebec - Office of the Surveyor General (Compiler, Printer)
Consists of the locations and designations of Indian reserves in the North West Territories and the Province of Quebec. This map was an evidentiary exhibit in a case in the Supreme Court of Canada. Indian reserves in the North West Territories are denoted by circles, while reserves in Quebec are denoted by squares. Innu communities are labelled by name. Some railroad routes are visible throughout. Scale 1:1,150,000 Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .